Egypt's position on the Eritrean-Ethiopian conflict during 1977-1981 (Journal of the College of Basic Education, 2023)
Egypt has witnessed many fluctuations in its foreign policy with the change of presidents, each president comes pursuing a foreign policy governed in many cases by international and regional developments in that period, and Egypt has adopted multiple positions on the Eritrean-Ethiopian conflict since the Eritrean revolution and its demand for complete independence from Ethiopia, and from the solution of our research this we cast light on Egypt's position on the Eritrean-Ethiopian conflict for the period from 1977 to 1981, where that period witnessed a noticeable variation in the Egyptian position, so we see it in favor of Eritrea It provides financial and popular support to it based on its support for liberation movements in Africa and many countries of the world, and once again it takes the character of neutrality and intervenes to bring the views of the two parties to the conflict closer, and again it supports the Ethiopian party against Eritrea. The division of our research for several axes, where the first axis included the position of the conflict during the years 1877 to 1979, the second axis included the problem of water and its impact on the Egyptian position in that period, while the third axis talked about the position of the Egyptian during the years 1980-1981, a period in which the end of the rule of Egyptian President Mohamed Anwar Sadat.